Prevalence and abundance of traditional and host-associated fecal indicators in urban estuarine sediments: Potential implications for estuarine water quality monitoring. (1st October 2020) - Ahmed, Warish; Payyappat, Sudhi; Cassidy, Michele; Harrison, Nathan; Marinoni, Oswald; Besley, Colin
Abstract: This study aimed to determine the prevalence and abundance of sewage and animal fecal contamination of sediment at seven estuarine locations in Sydney, NSW, Australia. Sediment samples were tested for the occurrence of microbial targets including molecular marker genes of enterococci (ENT), Bacteroides HF183 (HF183), Methanobrevibacter smithii ( nifH), human adenovirus (HAdV) and emerging sewage-associated marker genes crAssphage (CPQ_056) and Lachnospiraceae (Lachno3) and animal feces-associated marker genes, including avian feces-associated Helicobacter spp. (GFD), canine-feces associated Bacteroides (DogBact), cattle-feces associated (cowM2) and horse feces-associated Bacteroides (HoF597). Results from this study showed that urban estuarine sediment can act as a reservoir of fecal indicator bacteria (FIB) and several microbial source tracking (MST) marker genes, including previously unreported Lachno3. The sewage-associated marker gene CPQ_056 was most prevalent, in 63.8% of sediment samples, while the avian associated marker gene GFD had the highest mean abundance. The GFD marker gene was highly abundant and widely detected in sediment samples from all seven locations compared to the other animal feces-associated marker genes. In all, 31 (44.9%) sediment samples were positive for at least two sewage-associated marker genes. However, the non-quantifiable detection of the HAdV marker gene did not always align with the detection of two or more sewage-associated marker genes. In addition, the most frequent wet weather overflow exposure occurred at locations that did not have a consistent pattern of detection of the sewage-associated marker genes, suggesting sediments may not be a suitable measure of recent sewage contamination. To assist water quality and public health managers better understand past microbial contamination of estuarine sediment, further studies seem justified to explore the role of decay of MST marker genes in sediment. Further work is also needed on the role of resuspension of MST marker genes from sediment during storm events to the water column as a source of contamination for both the GFD and sewage-associated marker genes. Highlights: The crAssphage marker gene was detected in 63.8% of sediment samples. The avian marker was highly abundant and widely detected in sediment. Adenovirus did not always align with the detection of two or more sewage markers. The prevalence of the sewage marker genes did not align well with wet weather overflows.